Behaviour of RC deep beams with web openings at the top of shear span near support - Ain Nasuha, Mohd Talib (2014)
This thesis deals with behaviour of RC deep beams with web openings at the top of shear span near support. The objectives of this thesis are to determine load deflection curve and crack pattern of RC deep beams with openings, identify the effects of opening size and shape and lastly comparing finite element analysis results with experimental results. In this thesis, two types of opening shapes were studied. The first one was circular and the other one was square. The opening sizes used were 150x150 mm, 200x200 mm and 250x250 mm. The structural twodimensional solid modeling of deep beams was developed using ATENA software. The finite element model of the structure was analyzed using nonlinear behaviour approach. Reinforcements used were 16 mm, 10 mm and 6 mm. Finally, crack pattern and load deflection curve which comprises of yield load, ultimate load and deflection of beam were obtained. Location of stress concentration could be detected. From the results, similar crack pattern was observed in beams with openings, both circular and square. All beams are failed in the same manner with diagonal cracks formed at the opening corner in square opening and around the circular opening. Beams failed in shear mode. As the opening size increases, beam capacity of deep beam decreases. For solid beam, the ultimate load is 65.09 kN. When comparing load capacity for deep beams with web openings, deep beam with 150x150 mm size opening has a higher ultimate load capacity compared to deep beam with the opening size of 200x200 mm and 250x250 mm. The ultimate load capacity decreases in the range of 47.76% to 73.31% as compared to control beam. Similarly, increasing in diameter of circular opening from 0150 mm to 0200 mm and 0250 mm has reduced the ultimate load capacity of beam, about 34.98% to 56.08%. This signifies beam with circular opening demonstrate higher beam capacity as compared to square opening. Load deflection curve trend was observed to behave elastically under gradually increase load up to elastic limit and load decreased in plastic deformation phase. The results obtained from experimental work and finite element analysis in terms of ultimate load indicated close values. The highest percentage of difference was 56.53% due to the presence of square opening with the size of 240x240 mm. Whereas about 2.10% difference was observed in the results of beam with circular opening of 250 mm diameter. For crack pattern, fair agreement was observed between experimental work and FE analysis.